KORELASI KREATIVITAS GURU DALAM MENGAJAR TERHADAP PRESTASI BELAJAR SISWA SDN 25 DOMPU - Mulya Yusnarti; Dedi Kusnadi (Jurnal Pendidikan Dasar Borneo (Judikdas Borneo), 2021)
Abstract: This study aims to determine the creativity of teachers in teaching learning achievement of students at SDN 25 Dompu. Data collection methods used were questionnaire and test. The data analysis technique used in this study is to use the Product Moment formula. Based on the results of data analysis that teacher creativity in teaching has a significant relationship with student achievement, this is indicated by the relationship of teacher creativity with student achievement from rxys count as big as 0.507 categories, teacher creativity contributes to student achievement by 25.70% and the remaining 74.30% is determined by other variables. It is proven that there is a significant relationship between teacher creativity and student learning achievement, it is calculated that 3.6733 is greater than the value of t-table 1.6828 or (3.6733 1.6828) according to the number of n = 41 At the 5% significance level or the 95% confidence level (table r product moment attached). This shows that the null hypothesis (Ho) which reads "There is no relationship between the creativity of teachers in teaching with the learning achievement of fourth grade students at SDN 25 Dompu '', is rejected, and the alternative hypothesis (Ha) which reads" there is a relationship between teacher creativity in teaching and learning achievement of fourth grade students at SDN 25 Dompu ”, acceptedAbstrak: Penelitian ini bertujuan untuk mengetahui korelasi kreativitas guru dalam mengajar terhadap prestasi belajar siswa SDN 25 Dompu. Metode pengumpulan data yang digunakan yaitu angket dan tes.Teknik analisis data yang digunakan dalam penelitian ini adalah dengan menggunakan rumus Product Moment.Berdasarkan hasil analisis data bahwa kreativitas guru dalam mengajar memiliki hubungan yang signifikan dengan prestasi belajar siswa, Hal ini ditunjukan dengan hubungan kreativitas guru dengan prestasi siswa dari hitung rxysebesar 0.507 kategori cukup kuat, kreativitas guru memberikan konstribusi terhadap prestasi belajar siswa sebesar 25,70% dan sisanya 74,30% ditentukan oleh variabel lain. Terbukti bahwa ada hubungan yang signifikan kreativitas guru dengan prestasi belajar siswa, ternyatat-hitung 3.6733 lebih besar dari nilai t-tabel 1.6828 atau (3.6733 1.6828) sesuai dengan jumlah n = 41 Pada taraf signifikansi 5% atau taraf kepercayaan 95% (tabel r product moment terlampir).Hal ini menunjukkan bahwa hipotesis nihil (Ho) yang berbunyi “Tidak ada hubungan antara kreativitas guru dalam mengajar dengan prestasi belajar siswa kelas IV di SDN 25 Dompu’’, ditolak, dan hipotesis alternatif (Ha) yang berbunyi “ada hubungan antara kreativitas guru dalam mengajar dengan prestasi belajar siswa kelas IV di SDN 25 Dompu”, diterima